2002
DOI: 10.1109/joe.2002.1002481
|View full text |Cite
|
Sign up to set email alerts
|

Power system considerations for undersea observatories

Abstract: Power systems for undersea observatories combine ideas from terrestrial power systems and switching power supplies with experience from undersea cable systems. Basic system tradeoffs for various design decisions are explored in this paper. First, design questions including whether the power delivery should be alternating or direct current and a parallel or series network are examined. This introduces the question of maximum power delivery capability, which is explored in depth. A separate issue, the negative i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(31 citation statements)
references
References 10 publications
0
31
0
Order By: Relevance
“…Use scenarios where 10 kW per node are required can easily be constructed. However, Howe et al (2002) showed that the power which can be delivered over a COTS submarine telecommunications cable network will be limited by the electrical characteristics of the cable. For the NEPTUNE regional cabled observatory, simulations showed that 5 kW could be delivered to each of 26 nodes using two shore connections, but 10 kW could be delivered to only a few at a time with reduced power available for the rest.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Use scenarios where 10 kW per node are required can easily be constructed. However, Howe et al (2002) showed that the power which can be delivered over a COTS submarine telecommunications cable network will be limited by the electrical characteristics of the cable. For the NEPTUNE regional cabled observatory, simulations showed that 5 kW could be delivered to each of 26 nodes using two shore connections, but 10 kW could be delivered to only a few at a time with reduced power available for the rest.…”
Section: Discussionmentioning
confidence: 99%
“…The key engineering tradeoffs that guide decisions about ocean observatory power are reviewed by Howe et al (2002). They describe the technical difficulties that an underwater AC power system present, and show that DC power provides a significant cost advantage.…”
Section: A Generic Cabled Ocean Observatorymentioning
confidence: 99%
See 1 more Smart Citation
“…Armoring varies dependent on bottom lay conditions. Up to ten kilowatts of shore power will be stepped down on the seafloor to deliver 48 volts DC to instruments (Howe et al, 2002). Multiple ports will be available for wet mateable connections to instruments that may extend several kilometers from the conversion node.…”
Section: Oceanographic Features Of the Regionmentioning
confidence: 99%
“…The electrical Ethernet signal is changed into optical signal and sent to the subsea platform through optical fibers in the coaxial cable along with high voltage power delivered via copper conductors of the coaxial cable. Transmitting power in high DC voltage is mainly because it can reduce power loss on cable [12][13]. The coaxial cable lay along the seafloor and reaches to the scientific interesting area where a science platform is fixed.…”
mentioning
confidence: 99%